2021
DOI: 10.3390/polym13081245
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Poly(Ethylene-glycol 1,4-Cyclohexane Dimethylene-Isosorbide-Terephthalate) Electrospun Nanofiber Mats for Potential Infiltration of Fibroblast Cells

Abstract: Recently, bio-based electrospun nanofiber mats (ENMs) have gained substantial attention for preparing polymer-based biomaterials intended for use in cell culture. Herein, we prepared poly(ethylene-glycol 1,4-Cyclohexane dimethylene-isosorbide-terephthalate) (PEICT) ENMs using the electrospinning technique. Cell adhesion and cell viability of PEICT ENMs were checked by fibroblast cell culture. Field emission electron microscope (FE-SEM) image showed a randomly interconnected fiber network, smooth morphology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Raman spectrum also confirmed the presence of C=O, N-C=O and increased CH 2 at 1781 cm −1 , 1658 cm −1 and 1425 cm −1 , respectively. As per previous reports, increased number of CH 2 groups on polymeric fiber's surfaces results in increased cell adhesion properties, which indicates the potential for cell culture applications of this optimized cage-type blend with 5% SuPMA content [59].…”
Section: Physico-chemical Properties Of Pga Collagen and Their Blend Nanofiberssupporting
confidence: 87%
“…Raman spectrum also confirmed the presence of C=O, N-C=O and increased CH 2 at 1781 cm −1 , 1658 cm −1 and 1425 cm −1 , respectively. As per previous reports, increased number of CH 2 groups on polymeric fiber's surfaces results in increased cell adhesion properties, which indicates the potential for cell culture applications of this optimized cage-type blend with 5% SuPMA content [59].…”
Section: Physico-chemical Properties Of Pga Collagen and Their Blend Nanofiberssupporting
confidence: 87%
“…It was found that the PEICT nanofibers possessed excellent biocompatibility. Hence, the results confirmed that PEICT ENMs can potentially be utilized as a biomaterial [ 29 ]. Silver nanoclusters are also considered excellent antibacterial agents; another study in this Special Issue synthesized novel sericin-encapsulated silver nanoclusters (sericin-AgNCs) through a green synthesis route.…”
supporting
confidence: 60%
“…In addition, keratinocytes covered the scaffold surface through cellular layers, which is indicative of epithelization capacity. We have recently disclosed the immunomodulatory activity of other PHA/OLE fibers in vitro using human dermal keratinocytes occurring via the downregulation of the inflammatory pattern, thus proving the potential for skin re-epithelization and regeneration, which are secondary to inflammation resolution [ 45 ].…”
Section: Discussionmentioning
confidence: 99%